Comparative analysis of phraseological units of Body parts lexico-semantic field (on the material of Arabic, Avar and Russian languages) - Z I Ismailova (Russian journal of linguistics: Vestnik RUDN, 2011)
The article attempts to study phraseological units with somatic body parts component of the Arabic language in comparison with Аvar and Russian languages. The paper covers the following problems: the comparison of phraseological units of three unrelated languages, the exposure of semantic peculariaties of analyzed somatic phraseological units, the description of structural-grammatical composition of Arabic, Avar and Russian somatic phraseological units, the research of interlanguage equivalence of somatic phraseological units in compared languages.